Prevalence of measles antibodies among migrant workers in Singapore: a serological study to identify susceptible population subgroups - Ang, Li Wei (2022)
Background: In 2019, two clusters of measles cases were reported in migrant worker dormitories in Singapore. We conducted a seroprevalence study to measure the level of susceptibility to measles among migrant workers in Singapore. Methods: Our study involved residual sera of migrant workers from seven Asian countries (Bangladesh, China, India, Indonesia, Malaysia, Myanmar and the Philippines) who had participated in a survey between 2016 and 2019. Immunoglobulin G (IgG) antibody levels were first measured using a commercial enzyme-linked immunosorbent assay (ELISA) test kit. Those with equivocal or negative IgG results were further evaluated using plaque reduction neutralization test (PRNT). Results: A total of 2234 migrant workers aged 20–49 years were included in the study. The overall prevalence of measles IgG antibodies among migrant workers from the seven Asian countries was 90.5% (95% confidence interval 89.2–91.6%). The country-specific seroprevalence ranged from 80.3 to 94.0%. The seroprevalence was significantly higher among migrant workers born in 1965–1989 than those born in 1990–1999 (95.3% vs. 86.6%, p < 0.0005), whereas there was no significant difference by gender (90.8% in men vs. 89.9% in women, p = 0.508). 195 out of 213 samples with equivocal or negative ELISA results were tested positive using PRNT. Conclusion: The IgG seroprevalence in migrant workers was below the herd immunity threshold of 95% for measles. Sporadic outbreaks may occur in susceptible individuals due to high transmissibility of measles virus. Seroprevalence surveys can help identify susceptible subgroups for vaccination.